A New Wave of ECB's Unconventional Monetary Policies : Domestic Impact and Spillovers - Varghese, Richard (IMF Working Papers; Working Paper ;, 2018)
ECB President Draghi's Jackson Hole speech in August 2014 arguably marked a new phase of unconventional monetary policies (UMPs) in the euro area. This paper examines the market impact and tranmission channels of this new wave of UMPs using a modified event study framework. They are found to have a more prominent impact on inflation expectations and exchange rates compared to the earlier UMP announcements. The impact on bank equity, however, is less significant in part due to narrowing profit margin in a low interest rate environment; and the marginal effect on sovereign spread compression has diminished. By extracting components of monetary policy shocks from the yield curve, we find that the traditional signaling channel of the monetary policy transmission continued to play an important role, but the portfolio rebalancing channel became more important in the new phase. Spillovers to non-euro area EU countries (the Czech Republic, Denmark, Poland, and Sweden) are transmitted mainly through the portfolio rebalancing channel, largely affecting sovereign yields and exchange rates.